Entomologische Untersuchungen der Fluss Mur (Mura) am Beispiel der Käfer (Coleoptera) - Drovenik, Božidar (Acta entomologica slovenica (Ljubljana), 2004)
Results of the faunistical studies of the beetles in the Mura river basin between Šentilj and the border with Croatia, carried out between 1992 and 1996, are presented. Previous knowledge of the beetles of this part of Slovenia was very poor. Only most valuable results are mentioned.
Keywords: Coleoptera; favna; hrošči; Mur; Mura